A TOGAF-based information governance model for the digital transformation of SMES - Nyoman Ayu Nila Dewi; I Ketut Widhi Adnyana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Digital transformation is key in business processes, including for Small and Medium Enterprises (SMEs). With digital transformation, a company can change the way it serves its customers, but this implementation carries high risks due to limited resources and management changes. SMEs often face obstacles in adopting new technologies, such as financial constraints, lack of technical skills, and barriers in technology implementation and human resources. Good IT governance is necessary for SMEs to survive technological developments. In general, business processes that already run are still done conventionally, thus governance needs to be implemented. From these problems, a strategic plan is needed that can produce a blueprint framework which is needed by the company. The findings of this study consist of TOGAF ADM-based architectural artifact documents, which serve as a foundation for identifying technology mappings that can be developed in alignment with the existing business processes of small and medium-sized enterprises (SMEs). A blueprint framework can be used by SMEs to determine the priorities and stages of system development over the next few years to be carried out, of course, by considering internal and external factors. From the results of the framework, the development of information systems for marketing and selling SME products is carried out to overcome problems such as the lack of knowledge of partners in marketing so that it has an impact on partner income. With structured IT governance, SMEs can align IT strategies with business goals and develop information systems that support business continuity in the future.